Dorsal Onlay Buccal Mucosal Graft Urethroplasty for Bulbar Urethral Stricture- Experience Of 20 Cases - Al Asad, Hafiz; Bhuiyan, AKM Musa; Islam, Md Nazmul; Karmaker, Uttam; Chowdhury, Md Shafiqul Alam; Saha, Prodyut Kumar; Hossain, AKM Shahadat; MahbubAlam, SM (Journal of Dhaka Medical College, 2015)
Objective: To assess the success of buccal mucosal graft (BMG) urethroplasty by the dorsal onlay technique in bulbar urethral stricture. Materials and Methods: FromJuly 2008 to June 2010, twenty patients with anterior urethral strictures weremanaged by dorsal onlay BMG urethroplasty. After voiding trial, they were followed up at 3 weeksand 3 months with history, physical examination, uroflowmetryand retrograde urethrogram (RGU) if required. Patients were furtherfollowed-up at 3 months interval with uroflowmetry and retrograde urethrogram (RGU) if required. Successfuloutcome was defined as normal voiding with no surgical intervention after catheter removal. Results: Mean stricture length was 3.5 ± 0.8 cm and mean follow up was 12 months (range 6 to 24 months). Twopatients were found to develop stricture at anastomotic site, during followup and required optical internal urethrotomy and was considered as failure.One patient developed wound infection which resolved after regular dressing. Success rate was 90%. Conclusion: Dorsal onlay BMG urethroplasty is a simple technique with good surgical outcome. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 175-178